6 months of radioxenon detection in western Europe with the SPALAX-New generation system – Part 2: Atmospheric transport modelling. (January 2021) - Achim, Pascal; Generoso, Sylvia; Topin, Sylvain; Gross, Philippe; Monfort, Marguerite; Moulin, Christophe; Le Petit, Gilbert; Douysset, Guilhem; Morin, Mireille
Abstract: Atmospheric transport modeling has been used to interpret the unprecedented number of multi-isotope detections of radioxenons observed during the six months of the qualification process by the Comprehensive Nuclear-Test-Ban Treaty Organization of the new SPALAX-NG system (Système de Prélèvement Automatique en Ligne avec l'Analyse du Xénon - Nouvelle Génération). Highest 133 Xe activity concentrations were found to be systematically associated with the concomitant measurement of several other radioxenons at the prevailing wind direction of north/northeast pointing to the Institute for Radio Elements (IRE), a medical isotope production facility located in Fleurus (Belgium). The lowest 133 Xe activity concentrations were not associated with a prevailing wind direction or other radioxenons, indicating the contribution of distant sources (global background). The IRE's average source terms for 133m Xe and to a lesser extent for 133 Xe (slightly overestimated by a factor of 1.7) showed good agreement with the literature values, while corrections by a factor of 23 and 53 were proposed for 131m Xe and 135 Xe since the initial values were underestimated. However, detections of 131m Xe alone and some low-activity concentrations of 133 Xe associated with only one of the other radioxenons could not be linked to the IRE releases. Analysis of these cases suggests the contribution of local source releases that have been difficult to identify to date. In addition to the global background, releases from such local sources, if not identified, could affect the analysis of the isotopic ratios measured following a nuclear test. The characterization of these local contributions is now possible owing to the capacity of the SPALAX-NG and other new generation measurements systems. Highlights: Atmospheric transport modeling was performed to interpret 6-month of atmospheric radioxenon monitoring by SPALAX-NG near Paris. An increased number of multi-isotope detections was recorded compared to SPALAX-1. Highest 133 Xe activity concentrations point to a medical isotope production facility. The lowest 133 Xe activity concentrations indicate the contribution of distant sources. Some 131m Xe or 135 Xe detections are due to local sources.